A Privacy-Preserving Spatial Index for Spatial Query Processing - Song, Doohee; Song, Moonbae; Park, Kwangjin (Wireless Communications and Mobile Computing, 2018)
An increasing amount of active research is being conducted to protect the locations of mobile device users. Users must tune to more data than they would like to in order to hide their location. In particular, if a user requests a query over kNN, the number of objects the user must receive may increase. Several studies have been proposed to solve these problems. However, problems have been identified during the course of query processing, such as errors and increased query processing times. When the tuning time is increased, the amount of data to download and the battery consumption of the client also increase. In this study, we propose the Privacy-preserving Spatial Index (PSI), an index that allows users to reduce their tuning time while being satisfied with the results of their queries. The querier (q) requests the object in the area protecting his/her location from the server. The server sends the requested data of points of interest (POIs) (DPOIs) in the Privacy-preserving Region (PR) to q. Finally, q reduces tuning time by selectively tuning to the desired data of POIs (Dw) through PSI. The superiority of PSI over previous techniques is experimentally proven.